ANÁLISE EPIDEMIOLÓGICA DOS EXAMES CITOPATOLÓGICOS DO COLO DE ÚTERO NO PARANÁ E 10ª REGIONAL DE SAÚDE DO PARANÁ DE 2013 ATÉ 2023 (REMUNOM, 2025)
Cervical cancer is one of the main types of cancer in women worldwide, and the cytopathological examination (Pap smear) is essential for its early detection. In Brazil, the state of Paraná has adopted the Pap smear as an essential strategy in the public health system, especially for women aged 25 to 64. This study analyzes data from cytopathological examinations performed between 2013 and 2023, focusing on the prevalence of cellular alterations among the female population of the state of Paraná and the 10th Health Region. The methodology adopted is descriptive and quantitative, using epidemiological records from SISCAN/DATASUS, with the objective of comparing cytopathological alterations between different age groups. The results show variations in the rates of low- and high-grade lesions and neoplasms, which were associated with the age of the patients. This epidemiological profile may support future public health policies aimed at the prevention and control of cervical cancer, promoting more targeted and effective interventions in the health of women in Paraná.